2012
DOI: 10.2337/db11-1300
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Metabolic Pathways in Aging

Abstract: Aging is characterized by a deterioration in the maintenance of homeostatic processes over time, leading to functional decline and increased risk for disease and death. The aging process is characterized metabolically by insulin resistance, changes in body composition, and physiological declines in growth hormone (GH), insulin-like growth factor-1 (IGF-1), and sex steroids. Some interventions designed to address features of aging, such as caloric restriction or visceral fat depletion, have succeeded in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
571
2
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 686 publications
(600 citation statements)
references
References 73 publications
10
571
2
17
Order By: Relevance
“…Thus, the inverse relationship observed between FGF21 and FGF19 in obesity and diabetes—upregulation of FGF21 and downregulation of FGF19—(Gallego‐Escuredo et al, 2015) did not occur in healthy elderly individuals, despite the significant increase in FGF21 (Figure 1a). Despite the absence of overt diabetes, our population of aged individuals showed an increase in glycemia and insulinemia relative to young individuals (Table 1), an observation previously reported and considered an indication of impaired functionality of general metabolic homeostasis with age (Barzilai, Huffman, Muzumdar, & Bartke, 2012). In fact, FGF21 levels were positively correlated with glucose levels ( r  = 0.197, p  = 0.048), insulin levels ( r  = 0.224, p  = 0.038), and insulin resistance, measured as HOMA‐IR, ( r  = 0.427, p  = 0.005) in the studied cohort.…”
supporting
confidence: 65%
“…Thus, the inverse relationship observed between FGF21 and FGF19 in obesity and diabetes—upregulation of FGF21 and downregulation of FGF19—(Gallego‐Escuredo et al, 2015) did not occur in healthy elderly individuals, despite the significant increase in FGF21 (Figure 1a). Despite the absence of overt diabetes, our population of aged individuals showed an increase in glycemia and insulinemia relative to young individuals (Table 1), an observation previously reported and considered an indication of impaired functionality of general metabolic homeostasis with age (Barzilai, Huffman, Muzumdar, & Bartke, 2012). In fact, FGF21 levels were positively correlated with glucose levels ( r  = 0.197, p  = 0.048), insulin levels ( r  = 0.224, p  = 0.038), and insulin resistance, measured as HOMA‐IR, ( r  = 0.427, p  = 0.005) in the studied cohort.…”
supporting
confidence: 65%
“…Clearly, disruption of the insulin/IGF‐1 signaling pathway in lower organisms extends lifespan, while a decrease in growth, and hence body size in mammals, is also linked to longevity (Barzilai et al ., 2012; Brown‐Borg & Bartke, 2012). However, while low peripheral IGF‐1 is linked to less cancer (Renehan et al ., 2004), it is associated with increased risk for other age‐related diseases in humans (Sonntag et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Diminished growth hormone/insulin‐like growth factor‐1 (GH/IGF‐1) signaling improves longevity across nature, including mice heterozygous for the IGF‐1 receptor (IGF‐1R) (Holzenberger et al ., 2003; Barzilai et al ., 2012). Moreover, low IGF‐1 action is relevant to humans because of its link to less cancer risk (Renehan et al ., 2004), an observation that spurred the development of IGF‐1R antagonists as a clinical cancer treatment (Pollak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the decreased activity, low concentrations, and small amounts of mRNA of insulin‐degrading enzyme in brains of patients with AD and knockout mice that lack the enzyme have reduced degradation of Aβ and insulin in brain (Lam & Lu, 2007; Li et al, 2002; Shanley, Irving, & Harvey, 2001). Similarly, insulin resistance is commonly observed in older adults (Barzilai, Huffman, Muzumdar, & Bartke, 2012; Morley, 2008). Insulin resistance usually caused the unrestrained hepatic gluconeogenesis, adipose lipogenesis, and defective glycogen synthesis and glucose uptake in skeletal muscle.…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 90%